From waste-activated sludge to algae: a self-reliant cultivation process in photoreactors using saline conditions. (6th April 2023) - Cao, Jinhua; Wang, Keli; Chen, Fanzhen; Li, Cheng; Gu, Yue; Fang, Zheng; Wang, Hao; Lu, Jingfang; Meng, Fansheng; Huang, Wenli; Liu, Dongfang; Wang, Shaopo
Abstract: In this study, microalgae–bacteria (MB) systems using saline conditions (3 and 5% salinity) were built in order to use waste-activated sludge (AS) as raw material for cultivating lipid-rich microalgae. Algae were observed to be flourishing in 60 days of operation, which totally used the N and P released from the sludge biomass. A prominent improvement of lipid content in MB consortia was obtained under algae growth and salinity stimulation, which occupied 119–136 mg/g-SS rather than a low content of 12.1 mg/g-SS in AS. Lipid enrichment also brought a 3.1–3.3 times total heat release (THR) in the MB biomass. The marine spherical algae Porphyridium, as well as filamentous Geitlerinema, Nodularia, Leptolyngbya were found to be the main lipid producers and self-flocculated to 23.0% (R1) and 33.5% (R2) volume under the effect of residue EPS. This study had a big meaning in not only waste sludge reduction but also in manufacturing useful bioenergy products. HIGHLIGHTS: Self-reliant MB consortia systems were built with 3 and 5% of saline water. MB consortia achieved 119–136 mg/g-SS lipid content. MB consortia had 3.1–3.3 times the total heat release than AS. MB consortia could self-flocculate to 23.0–33.5% volume. Spherical Porphyridium and filamentous Cyanobacteria used N and P from AS. Graphical Abstract